Design of an Internet of Things (IoT) based Early Fire Prevention System Due to LPG Gas Leakage Using NodeMCU ESP8266 Module - Atmiasri; Rufi'i; Habib Maulana (BEST, 2024)
Gas is a molecule that is unbound, shapeless, invisible, and can transform into liquid or solid forms. Liquified Petroleum Gas (LPG) has become a part of people's lives, especially in cooking, and there are many benefits to using LPG. However, there are dangers posed by leaks of LPG gas that can lead to house fires. Improper installation of regulators is one such risk. Preventive measures against fire hazards caused by leaks can be anticipated by using the design and construction of an Early Warning System for LPG Gas Leaks based on the Internet of Things (IoT) using the Blynk application with the NodeMCU ESP8266 module. This device is equipped with an MQ-2 sensor, a relay, a 12V DC fan, and the Internet of Things. The system works as follows: when the MQ-2 sensor detects the presence of LPG gas, the relay turns on the fan, which will remove the gas from the vicinity of the open flame on the stove. The system can be monitored through the Blynk IOT application, which also provides notifications